Eco-industrial parks in China: Current situation, problems and development suggestions - Xing, J.; Silva, J.; Almeida, I. (EurOMA(The 24th European Operations Management Association Conference), 2017)
The purpose of this research is to introduce the context of Eco-Industrial Parks?EIPs? in China, outline the current situation, analyze the success and failure aspects of EIPs, and, then, put forward some feasible development suggestions for China EIPs, from the perspectives of both circular economy and sustainable development. Research questions that arose from literature review led a secondary data analysis concerning challenges that EIPs practices face like economic growth, environmental protection and sustainable urbanization. The present study aims at stimulating more practitioners and researchers’ interest concerning EIPs since economic, social and ecological sustainability is a global concern.